Differential quadrature method for nonlinear fractional partial differential equations. Issue 6 (12th October 2018) - Saeed, Umer; Rehman, Mujeeb ur; Din, Qamar
Abstract : Purpose: The purpose of this paper is to propose a method for solving nonlinear fractional partial differential equations on the semi-infinite domain and to get better and more accurate results. Design/methodology/approach: The authors proposed a method by using the Chebyshev wavelets in conjunction with differential quadrature technique. The operational matrices for the method are derived, constructed and used for the solution of nonlinear fractional partial differential equations. Findings: The operational matrices contain many zero entries, which lead to the high efficiency of the method and reasonable accuracy is achieved even with less number of grid points. The results are in good agreement with exact solutions and more accurate as compared to Haar wavelet method. Originality/value: Many engineers can use the presented method for solving their nonlinear fractional models.